Міжнародний досвід впровадження електронного урядування - Тищенко, Олена (Видавництво Львівської політехніки, 2012)
The article is about international experience of implementation of e-Government systems. The research examines the main phases and the current state of e-Government in different countries and its efficiency for government and citizens.
Keywords: електронний уряд; електронне урядування; система e-Government; електронна демократія; інформаційне суспільство